Controlled preparation of phases in two-dimensional time crystals - Mukherjee,R; Kuros,A; Sacha,K; Mintert,F (Physical Review Research, 2021)
The study of phases is useful for understanding novel states of matter. One such state of matter aretime crystals which constitute periodically driven interacting many-body systems that spontaneouslybreak time translation symmetry. Time crystals with arbitrary periods (and dimensions) can berealized using the model of Bose-Einstein condensates bouncing on periodically-driven mirror(s). Inthis work, we identify the different phases that characterize the two-dimensional time crystal. Bydetermining the optimal initial conditions and value of system parameters, we provide a practicalroute to realize a specific phase of the time crystal. These different phases can be mapped tothe many-body states existing on a two-dimensional Hubbard lattice model, thereby opening upinteresting opportunities for quantum simulation of many-body physics in time lattices.